The Goal: A Process of Ongoing Improvement - and Goldratt, Eliyahu M.; Cox, Jeff (North River Press, 1992)
Over 2 million copies sold! Used by thousands of companies and hundreds of business schools! Required reading for anyone interested in the Theory of Constraints. This book, which introduces the Theory of Constraints, is changing how America does business. The Goal is a gripping, fast-paced business novel about overcoming the barriers to making money. You will learn the fundamentals of identifying and solving the problems created by constraints. From the moment you finish the book you will be able to start successfully addressing chronic productivity and quality problems.